2009
DOI: 10.1189/jlb.1008591
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 ligands augment cPLA2α activity and lead to enhanced leukotriene release in human monocytes

Abstract: Toll-like receptors (TLRs) play an important role in innate immunity. They detect pathogen-associated receptor patterns (PAMPs) and initiate subsequent immune responses. Present studies investigate the influence of TLR2 ligands on leukotrienes (LT) formation in human monocytes. LTs are proinflammatory mediators derived from arachidonic acid (AA), which is released from membranes by phospholipase A(2) (PLA(2)) enzymes. Pretreatment of MM6 cells with the TLR2 ligands LTA, FSL-1, or Pam(3)CSK(4) resulted in an up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 39 publications
4
24
0
Order By: Relevance
“…The activation of cPLA 2 a requires phosphorylation at multiple sites which can be regulated by p38 MAPK and ERK1/2 activation. Previous studies have indicated that ERK1/2 or p38 MAPK phosphorylates cPLA 2 a at Ser 505 and then promotes cPLA 2 a activity in several cell types (Qi and Shelhamer, 2005;Kikawada et al, 2007;Pavicevic et al, 2008;Lindner et al, 2009). Our data provide evidence that LPS triggered cPLA 2 a phosphorylation at Ser 505 through an ERK-dependent pathway, but not p38 MAPK (Figs.…”
Section: Discussionsupporting
confidence: 56%
“…The activation of cPLA 2 a requires phosphorylation at multiple sites which can be regulated by p38 MAPK and ERK1/2 activation. Previous studies have indicated that ERK1/2 or p38 MAPK phosphorylates cPLA 2 a at Ser 505 and then promotes cPLA 2 a activity in several cell types (Qi and Shelhamer, 2005;Kikawada et al, 2007;Pavicevic et al, 2008;Lindner et al, 2009). Our data provide evidence that LPS triggered cPLA 2 a phosphorylation at Ser 505 through an ERK-dependent pathway, but not p38 MAPK (Figs.…”
Section: Discussionsupporting
confidence: 56%
“…Previously, the extracellular pattern recognition receptor TLR2 has been reported to activate cPLA2 (26). Moreover, the Leishmania surface molecule lipophosphoglycan (LPG) can interact with the macrophage-expressed TLR2 to modulate macrophage effector functions (27).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, TLR ligands have been shown to promote LT biosynthesis (37,38). Furthermore, both LTB 4 (39) and CysLTs (40) have themselves been reported to activate NF-κB in specific cells and contexts.…”
Section: Discussionmentioning
confidence: 99%